POLISEMI KATA ŻAKARA DALAM AL-QUR’AN - Muzaki, Mukhlash; Gina Najjah Hajidah (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
This scientific paper examines the diversity of meanings (polysemy) of the word żakara contained in the verses of the Qur'an. This scientific paper is written to find out the meaning of the word żakara both lexically, grammatically, and contextually. In compiling this scientific paper, the author used a qualitative method with a descriptive approach. The writing of this scientific work begins with comprehensive data collection. The data sources used are the digital Al-Qur'an with the translation version of the Ministry of Religion and the book of Ibn Kathir's interpretation to support contextual understanding and interpretation of verses. After data collection is complete, the author classifies the word "żakara" based on its function in the context of the verse. Furthermore, an analysis was conducted to identify the lexical, grammatical, and contextual meanings of the word in the context of the relevant verses. The results of this paper show that the word "żakara" in the Qur'an has at least 13 different meanings but these meanings are still related to each other. Key Word:  Polisemy, żakara, meaning